Building capacity for individual and systems-level collaborative conservation impacts: intentional design for transformative practice - Hauptfeld, Rina S., author; Jones, Megan S., author; Skyelander, Kim, author; Taylor & Francis Group, LLC, publisher (Colorado State University. Libraries, 2022)
Conservation for and with local communities and stakeholders is essential. Despite the importance of community-oriented approaches and calls for capacity building in conservation, the impacts and inputs of training in relational fields like collaborative conservation remain unclear. We used mixed methods to conduct one of the first evaluations of a collaborative conservation capacity building program, and present an empirically-based causal model of the programmatic inputs supporting long-term changes. We found moderate to transformational impacts on participants' practice and professional trajectories, and on multiple dimensions of capacity, including comfort, conviction, and identity. Flexible funding, immersion into a safe community of practice, and the obligation and opportunity to experiment with collaborative approaches fostered these changes. We also found evidence of a developing landscape of practice, and perceived benefits to communities where fellows worked. We suggest programs incorporate intentional design, including networked communities of practice and heuristics, to enhance individual and systems impact.
Keywords: capacity development; community of practice; conservation capacity; mixed methods; program design; program evaluation; social science